Is Bilateral Hallux Valgus Chevron Osteotomy a Safe Procedure for Ambulatory Surgery? - Morais, B (2022)
Introduction: Several osteotomies of the first metatarsal have been described for treatment of hallux valgus but chevron osteotomy is one of the most common and well-established procedure for treating this deformity. Although there is a trend towards considering bilateral surgery there is lack of publications addressing bilateral treatment in ambulatory units. The aim of this study is to analyze results of bilateral and unilateral distal chevron osteotomies associated with lateral soft tissue release as ambulatory procedures. Materials and methods: A retrospective review was made about the patients treated at our ambulatory unit over a period of five years. Initially, general information as patient's satisfaction's rate and return to normal activity's time and evaluation of standardized follow-up charts and records made by the surgeon were recorded. Secondly, the hallux metatarsophalangeal interphalangeal scale developed by the American Orthopedic Foot & Ankle Society was used. Results: A total of 194 patients with 230 feet operated were included in this study. We found 29 patients that didn't meet the inclusion criteria and were excluded. The unilateral group was composed by 139 feet and the bilateral group by 52 feet. The improvement between preoperative and discharge clinical and radiographic results was significant independently in both groups. A total of 14% of complications were found in our study, 19% in the unilateral group and 12% at the bilateral group. None of them required revision surgery. Conclusion: Bilateral distal chevron osteotomies, associated with lateral soft tissue release, are safe and effective ambulatory procedures. It was found a satisfactory deformity correction in moderate HV. Both patients that underwent unilateral and bilateral procedures had similar clinical and radiological outcomes with no increase in complications or return to normal activity time. With this study it was demonstrated that bilateral chevron osteotomies can be performed as ambulatory procedures.